RANCANG BANGUN ELECTRIC CONTAINER CRANE SEBAGAI SARANA BONGKAR MUAT DI TERMINAL PETIKEMAS BERBASIS PLC OMRON CP1E - Eddo Mahardika (Universitas Muhammadiyah Tangerang, 2018)
Port is one of the supporting infrastructure of sea transportation which is the gateway to and out of goods and passengers. The function and role of the port is very important one of them is the container terminal. The container terminal is where loading and unloading of goods in containers. At the container terminal the length of loading and unloading process is determined by the quality and quantity of the tool. One of them is container crane. Therefore designed a container crane model in the form of a prototype named electric container crane. At the time of design is used Programmable Logic Controller (PLC) Omron brand CP1E-E20SDRA type as a safety controller and add a double trolley system so that container cranes can be flexible in 4 slots without gantry movement, and also add automatic cable track system so container crane can be Moving without the need for a portable generator because it is supplied directly using electricity from PLN